The placenta: A site of end-organ damage after Fontan operation. A case series. (15th August 2019) - Phillips, Amanda L.; Cetta, Frank; Kerr, Sarah E.; Cheek, E. Heidi; Rose, Carl H.; Bonnichsen, Crystal R.; Phillips, Sabrina D.
Abstract: Background: Placental insufficiency may be the cause of the high preterm birth rate in women after Fontan operation. In this study we reviewed the clinical course and pregnancy outcome of women with Fontan physiology with a focus on placental pathology. Methods: We reviewed clinical charts and placental pathology from 7 women with Fontan physiology who had pregnancies at Mayo Clinic, Rochester, Minnesota. The review was limited to cases where placental pathologic specimens were rigorously examined. Results: Seven women had 13 deliveries between 2002 and 2018. Only 2 of 13 deliveries were at term (>37 weeks). Mean maternal age at time of last delivery was 27.5 ± 3.2 years. Preeclampsia was noted during 2 pregnancies and 2 women had preterm premature rupture of membranes at 24 and 35 weeks gestation, respectively. Placental abruption with bleeding occurred in 2 pregnancies. An additional 4 pregnancies were complicated by intrauterine growth restriction (IUGR). Median placental weight was 441.5 g (IQR 305.5–622.5 g). Median placental weight percentile for gestational age was 10th to 25th, but varied greatly; two placentas were <10th percentile and 5 were >90th percentile for gestational age. Two umbilical cords contained a single umbilical artery. Prominent subchorionic fibrin deposition was a consistent feature in all placentas. Villous hypermaturity was noted in 4 placentas. Conclusions: Fontan physiology may be associated with poor placental health. High systemic venous pressure and low cardiac output may contribute to stagnation of placental blood flow and result in subchorionic fibrin deposition and variable villous hypoplasia. This may explain the high preterm birth rate in women with Fontan physiology. Preterm deliveries and small-for-gestational-age (SGA) newborns should be anticipated in this patient population. Analysis of placental pathology may help determine both candidacy for future pregnancy and long-term effects of pregnancy for women with Fontan physiology. Highlights: Chronic hypoxemia, high systemic venous pressure and low cardiac output likely contribute to poor placental physiology. This may explain the high preterm birth rate in women after Fontan. Only 2 of 13 deliveries were at term (> 37 weeks). Preeclampsia was noted during 2 pregnancies, an 2 women had preterm premature rupture of membranes, 2 pregnancies had placental abruption with bleeding Prominent subchorionic fibrin deposition and villous hypoplasia were consistent features in these placentas